Gonadotropin-releasing hormone and conception of Holstein cows - Jeffrey S. Stevenson; M.K. Schmidt; Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1984)
To study the effects of gonadotropin-releasing hormone (GnRH) and timing of artificial insemination (Al) on fertility, 328 dairy cows were divided into four groups. Inseminations at first, second, or third service were done soon after detected estrus (0 hr) or 12 h later. One-half of the cows in each of the preceding groups received GnRH (100µg) or saline within 30 sec after AI. Conception at first service was not improved by GnRH. But conception rates at repeat services were improved by 21% when cows received GnRH after AI. Time of AI (0 vs 12 hr) had no effect on conception. Administering GnRH at repeat services should improve conception rate of lactating dairy cows.; Dairy Day, 1984, Kansas State University, Manhattan, KS, 1984;
Keywords: Kansas Agricultural Experiment Station contribution; no. 85-116-S; Report of progress (Kansas Agricultural Experiment Station); 460; Dairy; Gonadotropin-releasing hormone (GnRH); Conception rates; Artificial Insemination (AI)